Effects of fine fractions of soil organic, semi-organic, and inorganic amendments on the mitigation of heavy metal(loid)s leaching and bioavailability in a post-mining area. (May 2021) - Derakhshan Nejad, Zahra; Rezania, Shahabaldin; Jung, Myung Chae; Al-Ghamdi, Abdullah Ahmed; Mustafa, Abd El-Zaher M.A.; Elshikh, Mohamed Soliman
Abstract: This study investigated the effects of soil amendments including biomasses (rice husk, RRH and maple leaf, RML), biochar (rice husk biochar, RHB and maple leaf biochar, MLB), and industrial by-products (red mud, RM and steel slag, SS), at two application rates (0, 1, and 2% w/w) on leaching and bioavailability of heavy metal(loid)s (HMs) (As, Cd, Cu, Pb, and Zn) in the presence of an Asteraceae (i.e., lettuce). Physicochemical properties of the soil (i.e., pH, EC, CEC, and HMs leaching) and plants were examined before and after amending. The addition of amendments significantly (p < 0.05) increased soil EC (from 100 to 180 μScm −1 ) and CEC (from 7.6 to 15 meq100 g −1 ). Soil pH from 6.7 ± 0.05 increased about 2 units with increasing in the application rate of MLB, RM, and SS, while it decreased about 0.8 units in RML amended soil. Soil amendments reduced the easily leachable fractions (exchangeable and carbonate) of HMs in the order of MLB > SS > RM > RHB. The average concentration of Cd, Cu, Pb, and Zn in plant roots and shoots decreased >30 wt% in biochars and industrial by-products amended soils, while biomasses mitigated As uptake in lettuce. Results demonstrated that adding maple-derived biochar combined with revegetation effectively immobilized HMs in a post-mining area beside an induce in plant growth parameters. Graphical abstract: Image 1 Highlights: Effect of soil amendments varieties on metal(loid)s stabilization was investigated. Stabilization efficiency varied by amendments properties and metal(loid)s species. Alkaline amendments reduced the amount of easily-leachable fractions of metals. Biomass and biochar in soil induced plant growth, but reduced As uptake by lettuce. Maple biochar and steel slag showed the most stabilization efficiency for metals.